THE HUBUNGAN ANTARA TINGKAT PENGETAHUAN NYERI PUNGGUNG BAWAH TERHADAP PEMILIHAN FISIOTERAPI SEBAGAI CARA MENGATASINYA PADA PENGERAJIN UKIR KAYU DI DESA KETEWEL - Sintya, Ni Luh Made; Wibawa, Ari; Purnawati, Susy (Majalah Ilmiah Fisioterapi Indonesia, 2015)
The purpose of this research was to determine the relationship between the levels of knowledge of low back pain with physiotherapy selection as a way to anticipate low back pain among wood carver in Ketewel village. The research design was cross-sectional study done in May 2014 with the entire population of wood carver in Ketewel village who has fulfilled the inclusion and exclusion criteria. The wood carver selected by simple random sampling, and the corresponding formulas minimum number of samples obtained 97 samples. The results showed the dominant research subjects aged 40-49 years (33%), the status of high school education (52.6%) and had a good level of knowledge (53.6%) as much as 34% of the wood carver with a good level of knowledge turned out to choose a physiotherapist treatment in anticipate low back pain. The results of the analysis of the relationship between the level of knowledge of low back pain with physiotherapy selection as a way to anticipate it with the chi-square test, obtained value p = 0.022 (p < 0.05), which means there is a significant relationship between the level of knowledge of low back pain with physiotherapy selection.
Keywords: Knowledge Level of Low Back Pain, Physiotherapy